ASOSIASI VEGETASI TANAMAN RAMBATAN KETAK (Lygodium circinatum (Burm.)Sw.) di KPHL RINJANI BARAT, PULAU LOMBOK, NUSA TENGGARA BARAT - Endah Wahyuningsih; Eny Faridah; Budiadi Budiadi; Atus Syahbudin (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2019)
Ketak (Lygodium circinatum (Burm.) Sw.) is a fern plant and its growth requires other plants as a host plant for climbing of tendrils to get light. Information of vegetation association of host plant is needed, due to it is considered to have an influence on fern growth and productivity. This data and information is important to develop a strategy of ketak cultivation. This research was aimed to determine vegetation association of ketak host plant in its habitat. The study used purposive systematic sampling by survey technique based on altitude i.e. 0-249, 250-499 and 500-750 m asl. There are 10 of observation plot with dimension of 20 m x 20 m. In each plot, an analysis of vegetation association of ketak host plant to determine association between species, type of interaction and index of association between species of ketak host plant. The results showed that the vegetation association of ketak host plants in each altitude classification which had a positive and strong association are 7 pairs species in altitude of 0-249 m asl. and altitude 250 – 499 m asl., and 10 pairs species in the altitude 500 – 750 m asl.